2018
DOI: 10.1002/cm.21457
|View full text |Cite
|
Sign up to set email alerts
|

In vivo analyses of radial spoke transport, assembly, repair and maintenance

Abstract: Radial spokes (RSs) are multiprotein complexes that regulate dynein activity. In the cell body, RS proteins (RSPs) are present in a 12S precursor, which enters the flagella and converts into the axoneme-bound 20S spokes consisting of a head and stalk. To study RS dynamics in vivo, we expressed fluorescent protein (FP)-tagged versions of the head protein RSP4 and the stalk protein RSP3 to rescue the corresponding Chlamydomonas mutants pf1, lacking spoke heads, and pf14, lacking RSs entirely. RSP3 and RSP4 mostl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 46 publications
(95 reference statements)
5
22
0
Order By: Relevance
“…According to the supply‐limitation model, cilia will grow until the cell body pool of ciliary precursors is exhausted. The availability of cargoes, therefore, regulates IFT cargo loading and cilia length 50 . Our results are also consistent with this model, where we show basal body targeted DIAPH1 caused elongation or the formation of bulbs at the tips of cilia, probably owing to their ability to traffic vesicles and cargo to the base of the cilia.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…According to the supply‐limitation model, cilia will grow until the cell body pool of ciliary precursors is exhausted. The availability of cargoes, therefore, regulates IFT cargo loading and cilia length 50 . Our results are also consistent with this model, where we show basal body targeted DIAPH1 caused elongation or the formation of bulbs at the tips of cilia, probably owing to their ability to traffic vesicles and cargo to the base of the cilia.…”
Section: Discussionsupporting
confidence: 91%
“…As well, our findings that neither actin polymerization nor microtubule stabilization mutants of DIAPH1 rescue ciliation suggests that both functions of DIAPH1 are important in this process. Other studies have shown that changes in either actin or microtubule networks can influence cilia length by changing the level of soluble tubulin 49 or regulating the trafficking of vesicles to the base of cilia 50 …”
Section: Discussionmentioning
confidence: 99%
“…Compared with other radial spoke proteins (RSPs), spoke HSP40 is unusual. Axonemal components are imported from the cell body and then assemble at the microtubule plus ends at the flagellar tip (Rosenbaum and Child, 1967; Johnson and Rosenbaum, 1992; Lechtreck et al ., 2018). In general, components in an axonemal complex are first packaged into a precursor complex in the cell body (Fowkes and Mitchell, 1998; Qin et al ., 2004) and then delivered by anterograde intraflagellar transport (IFT) trains to the tip for the final assembly (reviewed by Rosenbaum and Witman, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…, 1996; Viswanadha et al. , 2014), radial spokes (Johnson and Rosenbaum, 1992; Lechtreck et al. , 2018), dynein regulatory complexes (DRCs; Bower et al.…”
Section: Resultsmentioning
confidence: 99%
“…Incorporation of GFP-RSP4 and GFP-DRC4, which are both transported more processively and less retrogradely than IC2-NG, occurs preferably at the tip with little exchange along the length of flagella (Wren et al. , 2013; Lechtreck et al. , 2018).…”
Section: Discussionmentioning
confidence: 99%